A Facile Single-Phase-Fluid-Driven Bubble Microfluidic Generator for Potential Detection of Viruses Suspended in Air - Jia Man; Luming Man; Chenchen Zhou; Jianyong Li; Shuaishuai Liang; Song Zhang; Jianfeng Li (Biosensors, 2022)
Microfluidics devices have widely been employed to prepare monodispersed microbubbles/droplets, which have promising applications in biomedical engineering, biosensor detection, drug delivery, etc. However, the current reported microfluidic devices need to control at least two-phase fluids to make microbubbles/droplets. Additionally, it seems to be difficult to make monodispersed microbubbles from the ambient air using currently reported microfluidic structures. Here, we present a facile approach to making monodispersed microbubbles directly from the ambient air by driving single-phase fluid. The reported single-phase-fluid microfluidic (SPFM) device has a typical co-flow structure, while the adjacent space between the injection tube and the collection tube is open to the air. The flow condition inside the SPFM device was systematically studied. By adjusting the flow rate of the single-phase fluid, bubbles were generated, the sizes of which could be tuned precisely. This facile bubble generator may have significant potential as a detection sensor in detecting viruses in spread droplets or haze particles in ambient air.